Development of a traditional game “engklek” based on numeracy literacy to improve locomotor movements of elementary school students - Silvie Roikhatul Jannah; Nur Ahmad Muharram; Reo Prasetiyo Herpandika; Irwan Setiawan (Indonesian Journal of Research in Physical Education, Sport, and Health)
Background: Locomotor movement is crucial for elementary school students as it enhances their physical development, motor skills, and overall engagement in physical activities. However, the development of locomotor movements among elementary schools has not been associated with literacy and numeracy, so it is necessary to have a traditional game media that contains elements of literacy and numeracy to improve locomotor movements in elementary school students. Objective: This study aims to create a product in the form of a literacy and numeracy-based “engklek” game to improve locomotor movements of elementary school students. Methods: This study uses the research and development (R&D) method using the ADDIE model, which consists of 5 stages: analyze, design, develop, implement, and evaluate. The subjects of this study were upper-grade students of State Elementary School 3 Watudandang, namely classes IV and V (22 students). Result: The results of this study are (1) the percentage of assessment results from material experts is 100% with a very effective category to be used in the application of traditional games “Engklek” based on numeracy literacy; (2) the percentage of media expert assessment results is 100% with a very feasible category to be applied to upper-grade students in improving locomotor movements; and (3) the percentage of assessment results from students is 85% with a very feasible category to be applied to upper-grade students in improving locomotor movements. Conclusion: In conclusion, the traditional game “Engklek” based on numeracy literacy is practical and feasible for physical education teachers to use in improving locomotor movements.